Hopf Bifurcation Analysis for a Variant of the Logistic Equation with Delays - Chifan, Iustina (Université d'Ottawa / University of Ottawa, 2020)
This thesis contains some results on the behavior of a delay differential equation (DDE) with two delays, at a Hopf bifurcation, for the nonzero equilibrium, using the growth rate, r, as bifurcation parameter. This DDE is a model for population growth, incorporating a maturation delay, and a second delay in the harvesting term. Considering a Taylor expansion of the non-dimensionalized model, we find a region of stability for the nonzero equilibrium, after which we find a pair of ODEs which help define the flow on the center manifold. We then find an expression for the first Lypapunov coefficient, which changes sign, so we also find the second Lyapunov coefficient, allowing us to predict multi-stability in the model. Numerical simulations provide examples of the behavior expected. For a similar model with one delay (PMC model), we prove the Hopf bifurcation at the nonzero equilibrium is always supercritical.
Keywords: Hopf bifurcation; Time delay; Stability